Improving Reading Skills Class VI Muhammadiyah Gantiwarno Elementary School through Learning Video Media - Nurhayati, Nurhayati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the learning outcomes of grade VI students of Muhammadiyah Gantiwarno Elementary School on reading skills through instructional video media. The research conducted was Classroom Action Research which was conducted in three cycles, where each cycle consisted of one meeting. The method in this research is carried out in four stages, namely planning, acting, observing, and reflecting. In the first cycle the learning outcomes of students seen from the class average reached 74.78 with completeness of the learning outcomes of students reaching 60.87%, In cycle II the class average reached 76.09 with completeness of the learning outcomes of students reaching 69.56%, while in cycle III the average was Class average reached 82.17 with completeness of student learning outcomes reaching 78.36%. The conclusion in this study states that the use of instructional video media can improve the learning outcomes of grade VI students at Muhammadiyah Gantiwarno Elementary School, especially in reading skills.